Dose maximal acetylcholine dose into the left coronary artery affect the positive provoked spasm in the left circumflex artery?. Issue 7 (November 2019) - Sueda, Shozo; Fujimoto, Kaori; Sasaki, Yasuhiro; Sakaue, Tomoki; Kohno, Hiroaki
Abstract : Background: Positive provoked spasm in the left circumflex artery (LCX) is lower than that in the left anterior descending artery and right coronary artery (RCA). Patients and methods: We examined the provoked positive spasm in the LCX between the maximal acetylcholine (ACh) 100 μg period (January 1991 to July 2012, 1474 patients: the former period) and the maximal ACh 200 μg period (August 2012 to August 2018, 336 patients: the latter period). ACh was injected in incremental dose of 20/50/100/200 μg into the left coronary artery and of 20/50/80 μg into the RCA. Positive spasm was defined as at least 90% stenosis and usual chest symptoms or ischemic ECG changes. Results: Provoked positive spasm in the latter period was significantly higher than that in the former period (65.5 vs. 39.1%, P < 0.001). The positive spasm increase of RCA and left anterior descending artery was 143 and 159%, whereas the increase of LCX was 204%. Multiple-vessel spasm was also increased in the latter period. Conclusion: Maximal ACh dose into the left coronary artery may affect the positive spasm in the LCX and multiplevessel spasm.